An early-emercing explanatory heuristic promotes support for the status quo. [article]. - Hussak, Larisa; Andrei Cimpian
People often view their sociopolitical systems as fair and natural despite indisputable biases in their structure. Current theories of this phenomenon trace its roots to a motivation to alleviate anxiety and uncertainty. Here, we propose a complementary cognitive pathway for these system-endorsing attitudes. Specifically, we propose that the fundamental mechanisms through which people explain the world around them may also be a source of such attitudes. These explanatory processes are inadvertently biased to yield inherent or internal facts as explanations for a wide variety of social and natural phenomena, including sociopolitical patterns (e.g., Why are some people rich? Because they are really smart). In turn, this bias toward inherent attributions makes it seem that the observations being explained (such as the societal status quo) are legitimate and thus worthy of support. Four studies with participants as young as 4 years of age provided correlational and experimental evidence for the hypothesized link between explanatory processes and support for the status quo. These findings suggest that the tendency to endorse existing sociopolitical arrangements emerges partly on a foundation laid early in life by a basic component of human cognition.-- (from the authors)